Sir Philip Sidney on Universality and Antiquity of Poetry: A Study: Exploring Sir Philip Sidney's Views on Universality and Antiquity of Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Sidney has proved that by nature poetry imitates and its function is two fold to teach anddelight. Sidney‟s view on universality and antiquity of poetry is valid. Through Sidney‟s „ Apology forPoetry‟ we can prove that Wordsworth‟s nature poetry is more delightful and understanding thanRousseau‟s insightful philosophy of „ natural education.‟ Poetry is superior to Philosophy and History –this notion of Sidney is quite serious and philosophical in itself. Sidney showed that pastorals poetrytreats evils of tyranny and beauty of simple life , the elegiac moves rather pity than blame , the bitteriambic rubs the galled minds , the comic imitates the common error of our lives and want a great foil toperceive the beauty of virtue.